Predictors of driving practices among older drivers: two ethnic groups comparison in Peninsular Malaysia - Yeoh, Sok Foon; Chan, Benjamin Yin Fah; Syed Abdul Rashid, Sharifah Norazizan (Center for Promoting Ideas, 2011)
Background: The speed of aging has led to a considerable attention on traffic safety among older drivers. Objective: This study aims to determine the driving practices and identify predictor variables that significantly contribute to safe driving practices among older drivers in different ethnic groups at Peninsular Malaysia. Method: The cross-sectional design and face-to-face interview protocol was used to collect 400 respondents aged 50 years and over. Findings: Generally, older Malaysian drivers are practicing safe driving practices (M = 34.79, SD = 3.48). Results of multiple linear regression analysis indicated that 22.8% variance of driving practices was explained by six variables that also significant at correlation level (F = 9.508, p = 0.05). This study also found that different ethnicity group having different determinants of safe driving practices. Conclusion: The provided information about the determinants of safe driving practices and ethnic differences among older drivers can contributes knowledge in gerontology field. The collected information is also important to provide insights for road planning system and training programs to improve road safety among older drivers.